(untitled) (Journal of Universal Science Research, 2024)
Corporate Social Responsibility (CSR) has emerged as a crucial component of contemporary business practices, reflecting a growing recognition of the importance of ethical, social, and environmental considerations in corporate decision-making. In recent years, the concept of CSR has gained traction globally, with businesses increasingly acknowledging their role in contributing to sustainable development and societal well-being. As companies seek to align their operations with principles of responsible business conduct, understanding the extent and nature of CSR implementation within specific contexts becomes paramount. The objectives of this article are twofold: first, to assess the current state of CSR adoption in Uzbek companies, and second, to identify the key determinants and factors influencing CSR practices within this context. By undertaking a systematic analysis of CSR initiatives, this study aims to provide insights into the drivers, challenges, and potential pathways for enhancing CSR engagement among Uzbek companies. The significance of this article lies in its potential to inform stakeholders, including policymakers, businesses, investors, and civil society organizations, about the prevailing CSR landscape in Uzbekistan. By uncovering patterns of CSR implementation and discerning the underlying factors shaping these practices, this article seeks to contribute to the promotion of sustainable and responsible business conduct in the country.